A Review on Hybrid Fillers in Rubber Composites. Issue 6 (13th April 2018) - Abdul Salim, Zainathul Akhmar Salim; Hassan, Aziz; Ismail, Hanafi
ABSTRACT: This review article is aimed at reporting the recent development of hybrid fillers used in vulcanized rubber. This review will consider the synergistic effect of rubber hybrid composites that consist exclusively of conventional fillers; carbon black and/or silica as the primary filler, which are combined with secondary fillers from various sources. The discussions are mainly focused on the analyses and comparisons of the curing characteristics, morphology, and mechanical properties of the rubber composite-filled hybrid fillers. The compatibility and the existence of synergistic effects between the different types of fillers show the potential for development and application in rubber industries. GRAPHICAL ABSTRACT: